Philosophy - "Papineau, David (ed.)" (London, 2004)
Bringing Philosophy To A Contemporary Audience And Showing Its Vital Relevance To All Our Lives Today What Does It Mean For Something To Exist? What Is Truth? Are We Free To Choose How To Think Or Act? What Is Consciousness? Is Human Cloning Ethically Acceptable? These Are Just Some Of The Questions That Strike Right To The Heart Of What It Means To Be Human. This Important New Book Shows That Philosophy Equips The Reader With The Essential Tools Of Critical Thought To Challenge Themselves To Think About These Issues. With Its Highly Original Treatment, Combining Philosophical Analysis, Historical And Biographical Background And Through-Provoking Illustrations, It Simultaneously Informs And Stimulates The Reader. Philosophy Is Structured Thematically Dealing With Major Issues - World, Mind And Body, Knowledge, Faith, Ethics And Aesthetics, And Society. Interspersed Throughout The Themes That Run Through Philosophy, At Appropriate Interludes, Are Relevant Sections On The Great Thinkers And Their Influence, As Well As The Schools Or -ISMS To Which They Subscribed. Philosophy Offers Life-Changing Perspectives On What Really Matters.
Keywords: Philosophy